Relationships Between Childhood Health Experience and Depression Among Older People: Evidence From China - Yao, Min (Frontiers in Psychology, 2021)
Poor childhood experiences have been associated with depression in adulthood. But whether this association can be extended to older people’s life is unclear. History of parental mental health were from 2014 CHARLS Wave 3 (Life History Survey) data while other data were from 2011 CHARLS Wave 1 baseline data. 4306 participants were included. The depression was assessed by the Chinese version of Center for Epidemiologic Studies Depression scales (CES-D). Logistic regression model was used. More than 40% of older people suffered from depression. A quarter of them had poor childhood self-reported health. Nearly 20% of their mother had a history of poor mental health and more than 10% of their father had a history of poor mental health. Poor childhood health experiences were shown to be associated with higher odds of depression (good self-reported health OR: 0.732***, 95% CI: 0.633 - 0.847; poor mother’s mental health OR: 1.391**, 95% CI: 1.138 - 1.699; poor father’s mental health OR: 1.457**, 95% CI: 1.141 - 1.862). Older people in China suffered from high prevalence of depression. Older people in China with poor childhood health experiences had greater odds of suffering from depression. Assessing childhood health experiences may identify high risk of depression in older people.